The War Against Corruption in Albania - Balliu, Alesia (European Scientific Journal, ESJ, 2023)
Corruption is a challenge faced by the whole world, but the fight against it becomes even more emergent in certain regions, such as Southeast Europe, due to a high presence of organized crime, combined with mass spread poverty and low democratic tradition. Given that the countries of the region have already gotten the green light for EU candidacy status, corruption stands as one of the main conditions for this membership. Looking at the fight against corruption throughout the region, and placing Albania in a special perspective, this study aims to bring a comprehensive picture of the legal aspects of the fight against corruption in Albania, looking at the development of relevant legislation and its effects on implementation, as well as the way this establishes the country’s journey towards being part of the EU. From an additional element with adverse effects, corruption has become one of the mechanisms that put the system to work, and it is almost impossible to remodel this system if corruption still exists within it. Therefore, the “open war” against corruption has become a basic need and the central fight during the long recovery process of various countries that have gone through difficult transitional periods.